Action Goals of Extension Communication: New Perspectives - Joseph Seepersad (Journal of Applied Communications, 1986)
There are many ways to classify the tasks and activities of extension staff. A recent report (Electronic Task Force Report, 1985) categorizes extension functions as information delivery, educational delivery, and problem-solving.